2021
DOI: 10.3390/jmse9040370
|View full text |Cite
|
Sign up to set email alerts
|

Hemocyte Health Status Based on Four Biomarkers to Assess Recovery Capacity in American Lobster (Homarus americanus) after Exposure to Marine Diesel and Diluted Bitumen

Abstract: The growing transportation of petroleum products pose a significant risk of marine diesel or diluted bitumen (dilbit) spills at sea. Despite the economic importance of the American lobster, there have been few studies assessing the impact study of such a spill on their population. In the lobster industry, lobster quality is monitored according to the Brix index of hemolymph. In our research, the effectiveness of three other biomarkers operative in the industry was assessed in hemolymph during contamination (ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…These substances reach aquatic ecosystems through various routes, directly through the discharge of chemical compounds into water or more indirectly through residues that have accumulated into the soil, and as a consequence of a flood, rains, or land runoff, they reach water sources. Organisms affected by these xenobiotics exhibit increased DNA damage, increased reactive oxygen species’ production, and disturbances in the hemolymph composition and the number of existing hemocytes [ 24 , 25 ].…”
Section: Hemocytes’ Response To Xenobioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…These substances reach aquatic ecosystems through various routes, directly through the discharge of chemical compounds into water or more indirectly through residues that have accumulated into the soil, and as a consequence of a flood, rains, or land runoff, they reach water sources. Organisms affected by these xenobiotics exhibit increased DNA damage, increased reactive oxygen species’ production, and disturbances in the hemolymph composition and the number of existing hemocytes [ 24 , 25 ].…”
Section: Hemocytes’ Response To Xenobioticsmentioning
confidence: 99%
“…One interesting study investigating the effects of organic mercury on the hemolymph of M. galloprovincialis reported that a concentration of 10 −5 M could induce morphological changes by changing the hemocyte’s shape and number and also reducing its ability to conduct phagocytosis [ 25 ]. In an older study about ionic regulation in the crayfish Orconectes propinquus upon mercury exposure for a 14-day [ 27 ] period, the author observed a significant decrease in Na + and Ca + , with the difference that the Ca + concentration increased after the depuration period [ 27 ].…”
Section: Hemocytes’ Response To Xenobioticsmentioning
confidence: 99%